1997
DOI: 10.1016/s0029-7844(97)81427-5
|View full text |Cite
|
Sign up to set email alerts
|

Uterine problems discovered after presumed hysterectomy: the manchester operation revisited

Abstract: Patients who have undergone a Manchester operation may develop disease in the retained uterine corpus, which should be considered in the differential diagnosis of a pelvic mass.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 5 publications
0
7
0
Order By: Relevance
“…After assessment of these reports including reference lists of eligible studies, four studies and two case reports were found with data on 573 women [18][19][20][34][35][36]. All studies were retrospective.…”
Section: Study Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…After assessment of these reports including reference lists of eligible studies, four studies and two case reports were found with data on 573 women [18][19][20][34][35][36]. All studies were retrospective.…”
Section: Study Selectionmentioning
confidence: 99%
“…In one woman, after four dilatations of the cervix, an abdominal hysterectomy was performed. Hopkins et al reported on three patients with uterine disease (two with cancer) after a Manchester procedure in women who thought that their uterus had been removed in prior prolapse surgery, which made the differential diagnosis difficult [35]. Therefore, after cervical amputation, a risk of stenosis is present, which could influence the occurrence of alarming symptoms (vaginal blood loss) in the development of adenocarcinoma of the uterus.…”
Section: Surgical Proceduresmentioning
confidence: 99%
“…12, 13 We did not observe any patients with these problems after 5 years follow-ups, however, we gave to patients a detailed explanation of the procedures that had been performed and pelvic ultrasonography was carried out annually in the postmenopausal group in order to measure the endometrial thickness.…”
Section: Discussionmentioning
confidence: 98%
“…Tipton and Atkin [9] examined 82 premenopausal women 6 to 12 years after they underwent the Manchester operation and found that uterine carcinoma had developed in 2. Hopkins and colleagues [10] also reported on 2 patients in whom adenocarcinoma of the endometrium developed in the retained uterus after they underwent the Manchester operation. These 2 patients were lost to follow‐up, and the authors suspected that hysterectomies had been performed.…”
Section: Discussionmentioning
confidence: 99%